Medicinal plants and herbal medicines in the dental clinic: a literature review (Research, Society and Development, 2022)
The use of herbal medicines is an ancient practice, recognized and transmitted between generations. With the objective of carrying out a survey of the literature on the use of medicinal plants for the treatment of oral disorders, this work compiled experimental research articles and/or literature review, with full and free texts from PubMed, LILACS, SciELO and ScienceDirect, published in English or Portuguese, peer-reviewed, during 2018 to 2022, using as keywords: Medicinal plants, Phytotherapy and Dentistry. 216 works were identified; according to the eligibility criteria, 192 articles were excluded (57 duplicate works, 97 were not experimental research and/or literature review, and 38 articles were discarded after reading the title and abstract for not providing data on the comparison group), resulting in the final sample of 24 articles. According to the publications analyzed, several medicinal plants have antimicrobial, anti-inflammatory, and antifungal activity against the main oral microorganisms and some of the substances mentioned can be used as an antiseptic. In addition to the proven effectiveness, herbal medicines have shown therapeutic superiority over allopathic medicines, being a viable option in the treatment and control of oral diseases, however, the knowledge of health professionals about pharmacological action, adverse effects and contraindications of herbal medicines is crucial.